Doing Critical GIS - Mahmoudi, Dillon; Shelton, Taylor (ACME: An International Journal for Critical Geographies, 2022)
This special issue emerges from a two-day workshop of the same name, held on April 1stand 2nd, 2019, in Baltimore, Maryland. Inspired by the continued growth and purchase of theories and practices of critical mapping, this workshop began from the provocation: “what should the doing of critical GIS look like?” Avoiding any single, universalizing answer to this question, the diversity of contributors to this special issue is mirrored in the diversity of their responses. Through examinations of Indigenous, queer, and feminist mapping practices, new theoretical framings for critical mapping and new technologies for producing non-Cartesian maps, and approaches to participatory data collection and mapping (and the limitations thereof), the collected papers each present their own partial perspective on expanding what doing critical GIS can, and ought to, look like. Despite the variety of approaches offered up by the special issue’s constituent papers, this introduction frames these contributions through a focus on two general themes that run throughout these papers: (1) the mapping of presences, absences, and relations, and (2) rethinking the processes of mapping. Or, put slightly differently, what we map and how we map. Ultimately, while the papers in this special issue offer a number of different paths forward, there are similarly many paths still untaken when it comes to doing GIS critically, which offer countless opportunities for continued growth in this work moving forward.
Keywords: Critical GIS; Mapping; Geographic Thought; Geographic Methodology